(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Genital herpes simplex infection is a viral infection caused by the herpes simplex virus (HSV) type 1 or 2. This disease transmitted during close skin or mucus membranes contact with an infected person who is shedding the virus. Infections that are commonly spread by sex, especially vaginal intercourse, anal sex and oral sex. Objective: For detection of HSV by immunological and molecular methods. Methods: Two hundred (200) samples were collected from females attending the Gynecology Outpatient Department in the Al-Imamein Al-Kadhimein Medical City and Baghdad Teaching Hospital during the period from May 2014 to April 2015. Based on availability of full clinical information about each patient, high vaginal swabs were taken from females at different ages (15-54 years) representing patients group complaining of abnormal vaginal discharge with or without other symptoms. The Statistical Analysis System- SAS program was used to study the effect of difference factors in study parameters. Chi-square test was used to significant comparison between percentages in this study. Results: Each of the vaginal swabs collected were examined, was preserved at -20 °C for DNA extracts were analyzed. In RT-PCR, the rate of infection was in women with HSV, those with age group (25-34) years and (35-44) years were 50%. Conclusion: HSV infections were detected in genital tract infection in women; molecular methods are considered the gold standard for diagnosis, given the excellent sensitivities, specificities, rapid and accurate laboratory diagnosis of HSV. Keywords: Genital herpes, diagnosis, immunological, molecular study Citation: Ali MK, Hathal HD, Almoayed HA. Prevalence and diagnosis of genital herpes by immunological and molecular study. Iraqi JMS. 2018; Vol. 16(1): 4-7. doi: 10.22578/IJMS.16.1.2